Idiopathic infantile hypercalcaemia--a continuing enigma. Issue 7 (July 1984) - Martin, N D; Snodgrass, G J; Cohen, R D
Abstract : Seventy six children with documented Fanconi-type idiopathic infantile hypercalcaemia were studied and compared with 41 with the Williams-Beuren syndrome. Clinical comparison showed, as expected, very close similarities but also considerable differences, particularly in the severity of feeding problems and the degree of failure to thrive. The estimated incidence of idiopathic infantile hypercalcaemia alone has remained constant for the past 20 years, at approximately 18 cases per year in the United Kingdom (1 per 47 000 total live births). Long term morbidity in these children is mainly due to mental handicap and arteriopathy, but hypertension (29%), kyphoscoliosis (19%), hyperacusis (75%), and obesity (50%) may be added complications. In one child, hypercalcaemia recurred during adolescence but this seems to be excessively rare. More detailed investigation before treatment is required to discover the aetiology of hypercalcaemia in this condition.